Learnings from conducting mental health research during 2004 tsunami in Tamil Nadu, India - R. Padmavati; Vijaya Raghavan; Heather Rera; Megan Kearns; Kotteeswara Rao; Sujit John; R. Thara (BMC, 2020)
Abstract Background The Indian Ocean tsunami experience in 2004 caused a major loss of life and subsequent emotional trauma for survivors. Psychosocial needs in the aftermath of this disaster were extensive, yet the cohesion and effectiveness of response were limited due to lack of preparedness and relevant policy. The Schizophrenia Research Foundation (SCARF) was one of the organizations that quickly responded to provide psychosocial assistance to people in the tsunami affected areas and recognized a need for relevant research on disaster response. Therefore, we undertook research on the challenges, success and limitations of psychosocial interventions in alleviating post-traumatic symptomology. Discussion Both community-level workers and researchers were limited in their preparedness to carry out tasks related to response. Language barriers, cultural differences, and a gap in long-term services limited the breadth and scope of research that was able to be completed. Lack of policy, poor co-ordination of services, lack of trained researchers and limited resources were challenges that emerged during this period and various strategies were adopted to meet these challenges. Conclusions Continued research and evaluation of data has brought crucial considerations to light, including the variance in symptomology, effective tools of measurement, and the nuanced response of survivors. Future research should take relevant factors into consideration including barriers to care. Understanding of the local language and religious beliefs are significant resources in understanding the nature of survivors' trauma response and effective means of coping. Lastly, limitations regarding time frame and scope of research should be evaluated to provide more effective, comprehensive methods in future studies.